Resultados negativos asociados a medicamentos (MMS) en pacientes del servicio de medicina interna 7C en el Hospital Nacional Edgardo Rebagliati Martins en los meses de febrero-marzo 2012” - Cerna García, Julio César (2013)
The pharmaceutical care to hospitalized patients is a useful tool to improve the effectiveness of treatment, prevent problems and avoid diseases, thus unnecessary admissions that diminish the quality of life of patients and generate extra costs for the health system. It is important to rationalize health resources to ensure access to the service to patients who really need it. But drug treatment continues to be a problem in hospitalized patients, due to the large amount of drugs used for certain patients, many of whom are of narrow therapeutic. Because of these problems, the present study was conducted to identify those associated with Negative Results Medication patients 7C Internal Medicine at the Hospital National Edgardo Rebagliati Martins during the period of February-March, 2012, by the method Dàder. Accordingly it was determined that the main reason for admission to hospital was for high blood pressure, making 30% of the total. Pharmacotherapeutic monitoring results concerning potential interactions potential interactions were 2.6 per patient, which results in the type whose principal RNM safety, were a total of 51%. Finally it is concluded that the cardiovascular drug group with a higher rate of RNM, making a total of 42 % compared with the other groups.